Knowledge management of indigenous farmers of serrated mud crab fattening in the mangrove forest of La-NGU, Thailand - Kaewploy, Natpatcharakarn; Phonpakdee, Ratchadakorn; Poungsuk, Pakkapong; Siriwan, Nopakoon; Aquino, Marlowe Ubaldo (My University, 2020)
Knowledge management on indigenous farmers of serrated mud crab fattening in the mangrove forest of La-ngu, Thailand was in actual practice via activities of earning a living and daily life. There is a transfer of knowledge and dissemination among the people of the community on the basis of an agricultural society that is self-reliant. The process of local wisdom management consists of 6 steps: 1) the occurrence of problems or curiosity; 2) finding a guideline for solving the problems and increasing knowledge; 3) practice in the real situation; 4) an analysis of practice outcomes; 5) recapitulation of the body of knowledge; and 6) body of knowledge application and transfer.
Keywords: Communication; Indigenous; Knowledge management; Self-reliance; Serrated mud crab farmers